Primary cutaneous diffuse large B-cell lymphoma, NOS and leg type: Clinical, morphologic and prognostic differences - Felcht, Moritz; Klemke, Claus-Detlev; Nicolay, Jan Peter; Weiß, Christel; Géraud, Cyrill; Marx, Alexander; Goerdt, Sergij (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Background and objectives Primary cutaneous diffuse large B-cell lymphoma, NOS (PCLBCL/NOS) is a rare PCLBCL. Only few data are available for this tumor. The aim of this study was to identify clinical and/or immunohistochemical markers (in addition to Bcl-2) that characterize PCLBCL/NOS, assist in differentiating it from PCLBCL, leg type (PCLBCL/LT) and help to assess the clinical course/prognosis. Patients and methods Bcl-2- PCLBCL/NOS) cases (n = 14 were compared with Bcl-2+ PCLBCL/LT cases (n = 29). Results PCLBCL/NOS patients were younger, predominantly male and had better survival rates than patients with PCLBCL/LT. Patients with PCLBCL/NOS presented more often with larger plaques limited to one or two contiguous body regions, whereas PCLBCL/LT cases often presented with disseminated lesions. Neoplastic cells had a higher proliferation rate (Ki67) in PCLBCL/LT patients. The tumor microenvironment of PCLBCL/NOS had a more prominent CD3+ infiltrate. Overall survival data for the whole cohort (n = 37) revealed that female gender and Bcl-2 expression correlated with a worse survival rate. Bcl-6 expression and centroblastic subtype correlated with better outcomes. None of the other markers studied (e.g. GCB/non-GCB subtype) correlated with survival rate. Conclusions PCLBCL/NOS and PCLBCL/LT differ in their clinical behavior and outcomes. Bcl-2 still seems to be the best marker for discriminating between these two subgroups. Bcl-2, female gender and Bcl-6 represent prognostic markers for PCLBCL.
Gesehen am 12.06.2019